Connective Action in College Student Activism: Case Study of Indonesian College Student Demonstration in September 2019 - Rangga Kusumo; Aditya Perdana (Budapest International Research and Critics University, 2022)
After the 1998 Reform, the student movement in Indonesia Has more freedom to protest because it is guaranteed by the constitution. The Advances in technology are progressively making student movements appear to be more creative and involve various elements by utilizing social media. In September 2019, there were a series of student demonstrations centered in front of the Indonesian Parliament Building (DPR). The form of demonstrations was not only massively done in the field (offline), but also massively done on social media (online). This research uses a qualitative approach with a case study method. The research instrument used to obtain data is through interviews and literature studies. Referring to the theory of Bennet and Segerberg (2013) about connective action, this research found that there was a connection between the September 2019 student demonstrations with digital actions in the shape of personal action frames. The Twitter accounts that was identified, they were engaged in conversations on social media and expressed their personal attitudes through various forms, for examples were photos, videos, and posters. All of these accounts were related and created a collective cluster by means of the same hashtag and narrative, namely to reject the Draft Legislation of Criminal Code (RKUHP), revisions to the KPK Law and other Draft legislations those were deemed problematic. The student demonstration in September 2019 is included in the typology of organizationally-enabled action since it did not only occur massively in the field (offline), but also occured in a hybrid way in digital media (online). The formal structure, namely the Indonesian Student Alliance, had the role of coordinating actions in the field, as well as social media which led to open widely of participation from various groups to get involved in the action. Nevertheless, the massive digital action that occurred, was not the part in the design of the student movement, but happened organically and naturally.